Attitudes to illegal behaviour and conservation in western Tanzania. Issue 3 (5th September 2017) - Wilfred, Paulo; Milner-Gulland, E. J.; Travers, Henry
Abstract: Natural resources in and around protected areas in many countries in Africa are under intense pressure as a result of illegal behaviour, such as fishing, hunting and logging. A better understanding of local people's perceptions of the nature of illegal behaviour and the relevance of conservation actions would be useful in informing conservation decisions. We gathered information on the attitudes and perceptions of communities in the vicinity of Ugalla Game Reserve in western Tanzania regarding illegal behaviour and the effectiveness of conservation practices, using household surveys, key informants, and focus groups. We found that local people use the Reserve illegally, especially for hunting (28 ± SE 6%) and logging (20 ± SE 5%). We explored behaviours that are problematic for conservation in the partially protected areas around Ugalla. Local communities reported feeling isolated, harassed and intimidated by approaches used to protect Ugalla. They were angered by the conservation of Ugalla as a trophy hunting site for foreigners, and the excessive force and beatings used by game rangers to keep them away from the Reserve. Improving local livelihoods (17%), participatory conservation (16%), and giving people land for agricultural activities (16%) were among the ways that local communities felt would reduce illegal activities. Our findings suggest the need for conservation measures to benefit local communities around Ugalla transparently and equitably. Outreach programmes would help to raise conservation awareness and attract positive attitudes towards conservation. To encourage local support for conservation, we also suggest that conservation authorities create and maintain good relations with people living near the Reserve.